2020
DOI: 10.1038/s41467-020-19596-x
|View full text |Cite
|
Sign up to set email alerts
|

Broadband random optoelectronic oscillator

Abstract: Random scattering of light in transmission media has attracted a great deal of attention in the field of photonics over the past few decades. An optoelectronic oscillator (OEO) is a microwave photonic system offering unbeatable features for the generation of microwave oscillations with ultra-low phase noise. Here, we combine the unique features of random scattering and OEO technologies by proposing an OEO structure based on random distributed feedback. Thanks to the random distribution of Rayleigh scattering c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…22). The authors of [138] showed that, in this case, the plasmonic enhancement of the fields near the quantum dots did not occur and they were not excited (see ( 54)).…”
Section: Eqs Radiation Near Plasmonic Nanoparticles and Nanostructuresmentioning
confidence: 97%
See 2 more Smart Citations
“…22). The authors of [138] showed that, in this case, the plasmonic enhancement of the fields near the quantum dots did not occur and they were not excited (see ( 54)).…”
Section: Eqs Radiation Near Plasmonic Nanoparticles and Nanostructuresmentioning
confidence: 97%
“…22b). Analyzing the decay times of quantum dots in the presence of an Au nanocube and without it, one can estimate the Purcell factor, that turns out to be of the order of 30 [138]. In the same work, the autocorrelation function of emitted photons g (2) (0) ∼0.35 was investigated, showing that there is emission of single photons.…”
Section: Eqs Radiation Near Plasmonic Nanoparticles and Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…OEO has be developed to generate a variety of signals, such as the single-mode signal, frequency-scanning signal and the phase-coded signals. In 2020, Li Ming's team demonstrated for the first time that broadband random microwave signals can be generated by optoelectronic oscillation [5] . The work realized the generation of ultra-wideband (DC up to 40 GHz) random microwave signals by combining Rayleigh scattering effect and OEO structure.…”
Section: Introductionmentioning
confidence: 99%
“…Chew et al developed an OEO for a very precise temperature sensor [ 7 ]. Ge et al proposed an open cavity OEO to generate random microwave signals up to 40 GHz [ 8 ]. Fan et al created a photonic-delay line cross-correlation method for improving the used phase noise measurement of an OEO [ 9 ].…”
Section: Introductionmentioning
confidence: 99%